THE PERCEPTION OF FUTURE TEACHERS ON THE COMPETENCIES AND ROLES OF TEACHERS - Vali ILIE; Ecaterina Sarah FRĂSINEANU (Universitaria Publishing House, Craiova, 2023)
This research analyzes the students' perception of teachers' competencies and their roles in the educational activity. The study examines the issue starting from the theoretical and practical aspects offered by the specialized literature on this subject, based on the answers given by future teachers in the final year of their bachelor's degree about the characteristics of the 21st century teacher. The purpose of the research was to identify the main qualities of teachers (perceived by students), objectified in categories of professional competencies and roles. For this, we resorted to the content analysis (of some essays the students developed at the end of their first level of psychopedagogical training). The collection of the quantitative and qualitative results indicated a higher frequency of emotional and social competencies as well as that of the manager and counselor roles. The results showed that while some participants emphasized the educational support and others the role of socialization, most of them considered the emotional development to be first. Also, from the responses of the research participants, the critical areas that need to be developed in their professional training also emerge.